PENERAPAN MEDIA PEMBELAJARAN BERBASIS VIDEO ANIMASI PADA MATERI MAKROMOLEKUL UNTUK MENINGKATKAN HASIL BELAJAR SISWA DI KELAS XII SMA NEGERI 2 PASARWAJO - Zhio Husnayan; Saefuddin; Nada Shofa (STKIP Subang, 2026)
This study aimed to determine the effect of animation video-based learning media on students’ learning outcomes in macromolecule material and to identify students’ responses to the use of the media. The research was conducted at SMA Negeri 2 Pasarwajo in the 2025/2026 academic year using a quasi-experimental method with a Nonequivalent Control Group Design. The sample consisted of 29 students of class XII C as the experimental group and 28 students of class XII D as the control group selected through purposive sampling. The research instruments included learning outcome tests and student response questionnaires. Data were analyzed using descriptive statistics, the Shapiro-Wilk normality test, the Mann-Whitney test, and N-Gain analysis. The results showed that the average learning outcome score of the experimental class was 89.14, which was higher than that of the control class at 60.71. The N-Gain analysis revealed that the experimental class obtained an average score of 0.52, categorized as moderately effective, while the control class obtained an average score of 0.24, categorized as ineffective. The Mann-Whitney test yielded an Asymp. Sig. (2-tailed) value of 0.000 < 0.05, indicating a significant difference between the learning outcomes of the experimental and control groups. Furthermore, students’ responses to the use of animation video media were categorized as good to very good. Therefore, animation video-based learning media significantly improved students’ learning outcomes and can be used as an effective alternative learning medium for teaching macromolecule material.